TRPV4 activation triggers protective responses to bacterial lipopolysaccharides in airway epithelial cells. Issue 1 (December 2017) - Alpizar, Yeranddy; Boonen, Brett; Sanchez, Alicia; Jung, Carole; López-Requena, Alejandro; Naert, Robbe; Steelant, Brecht; Luyts, Katrien; Plata, Cristina; De Vooght, Vanessa; Vanoirbeek, Jeroen; Meseguer, Victor; et al.
Abstract Lipopolysaccharides (LPS), the major components of the wall of gram-negative bacteria, trigger powerful defensive responses in the airways via mechanisms thought to rely solely on the Toll-like receptor 4 (TLR4) immune pathway. Here we show that airway epithelial cells display an increase in intracellular Ca2+ concentration within seconds of LPS application. This response occurs in a TLR4-independent manner, via activation of the transient receptor potential vanilloid 4 cation channel (TRPV4). We found that TRPV4 mediates immediate LPS-induced increases in ciliary beat frequency and the production of bactericidal nitric oxide. Upon LPS challenge TRPV4-deficient mice display exacerbated ventilatory changes and recruitment of polymorphonuclear leukocytes into the airways. We conclude that LPS-induced activation of TRPV4 triggers signaling mechanisms that operate faster and independently from the canonical TLR4 immune pathway, leading to immediate protective responses such as direct antimicrobial action, increase in airway clearance, and the regulation of the inflammatory innate immune reaction. LPS is a major component of gram-negative bacterial cell walls, and triggers immune responses in airway epithelium by activating TLR4. Here the authors show that LPS also activates TRPV4, thereby inducing fast defense responses such as nitric oxide production and increased ciliary beating in mice.